Perencanaan Distribusi, Pemilihan Moda Transportasi, dan Kelancaran Pengiriman Bantuan Darurat Bencana - Rizky Noviyanti; Adri Yasman; Johanes Kurniawan Liauw (Institut Transportasi dan Logistik Trisakti, 2020)
The purpose of the study was to examine the effect of logistics distribution planning and the choice of transportation modes on the delivery of disaster emergency assistance. The data collection method used a survey of 30 BNPB employees as respondent. Multiple regression method was used in this research. The result shows that there is influence of logistics emergency distribution relief and the choice of transportation modes has a significant positive effect and a strong relationship on the smooth delivery of disaster emergency assistance.